Wear of large diameter ceramic-on-ceramic hip bearings under standard and microseparation conditions. (March 2020) - de Villiers, Danielle; Collins, Simon
Abstract: A novel Ceramic-on-Ceramic hip resurfacing implant offers a bone conserving treatment for young and/or active patients without the metal ion related issues associated with current Metal-on-Metal (MoM) hip resurfacing devices. BIOLOX delta ceramics are currently used as bearing surfaces in total hip replacement and have shown to be low wearing and biocompatible. Wear testing, however, has only been conducted in bearing diameters up to 36 mm and it is unknown how this material will perform tribologically and clinically in larger bearing diameters. The smallest (40 mm diameter) and largest (64 mm diameter) bearings of aceramic resurfacing implant size range were tested to ISO 14242-1 and ISO 14242-2 standards The largest size was also tested under microseparation wear conditions in a physiological hip simulator for 5 million cycles. The wear rate over the full 5mc was shown to not be influenced by the size of implant but at specific time points, there was a statistical significance, and in all cases steady state wear was low (≤0.5mm 3 /mc). The introduction of microseparation conditions increased the wear rate compared to standard conditions and produced stripe wear on the heads. The low wear and biocompatible nature of the BIOLOX delta material suggests it is a suitable material for use in hip resurfacing which may open this treatment option for patients who are currently not appropriate for MoM hip resurfacing. Highlights: BIOLOX delta (Zirconia Toughened Alumina) can be manufactured up to 64mm diameter for use in hip resurfacing. Over 5 million cycles, wear of ceramic-on-ceramic bearings larger than currently tested was less than 1 mm 3 Large diameter ceramic hip resurfacing bearings have comparable wear rates to smaller total hip replacement bearings BIOLOX delta is a suitable alternative material for hip resurfacing removing metal from the joint.